2021
DOI: 10.1002/wcms.1556
|View full text |Cite
|
Sign up to set email alerts
|

Understanding familial Alzheimer's disease: The fit‐stay‐trim mechanism of γ‐secretase

Abstract: Understanding Alzheimer's disease is a central challenge of the 21st century, as the disease affects tens of millions of people and kills a million people each year, with current drugs having modest effect. This article reviews how computational science integrating new cryo‐electron microscopy structures and biochemical and clinical data has led to a causative model of familial Alzheimer's disease (fAD). The model's basis is open and compact conformational states of the membrane protease γ‐secretase, controlle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
5
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 173 publications
(301 reference statements)
4
5
1
Order By: Relevance
“…The free energy landscapes and low-energy conformational states were explored in detail, which allowed us to deduce the effects of PS1 FAD mutants on the proteolytic activity of γ-secretase. Here, our main conclusion was that the PS1 FAD mutant γ-secretase stabilized the active sites of the enzyme-substrate complexes, which was distinctly different from previous studies, which suggested that PS1 FAD mutants destabilized the enzyme-substrate complexes, causing the earlier releases of longer Aβ peptides 10 , 22 , 42 45 .…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…The free energy landscapes and low-energy conformational states were explored in detail, which allowed us to deduce the effects of PS1 FAD mutants on the proteolytic activity of γ-secretase. Here, our main conclusion was that the PS1 FAD mutant γ-secretase stabilized the active sites of the enzyme-substrate complexes, which was distinctly different from previous studies, which suggested that PS1 FAD mutants destabilized the enzyme-substrate complexes, causing the earlier releases of longer Aβ peptides 10 , 22 , 42 45 .…”
Section: Discussioncontrasting
confidence: 99%
“…As the APP substrate was properly located inside the active site, its β3 strand (involving APP residues M51–K53) was formed through the hydrogen bonds with the β2 strand connected to PS1 TM7 (involving PS1 residues V379–L381) 50 . This finding was highly consistent with previous simulation studies, in which the repeated formations of β-strands in several solvent-exposed regions of presenilin were observed 22 , 43 , 51 , 52 . Afterwards, the catalytic aspartates D257 and D385 drew closer to each other, at a ~7–8 Å distance in the “Active” conformation, to recruit a water molecule poised for the proteolytic reaction (Fig.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our in silico analyses showing the coherent conversion of the GSM-GSEC-APP into the GSM-GSEC complex suggest the possibility that an equilibrium between these complexes exists and is regulated by the relative concentrations of the GSM and GSEC substrates. This strengthens the high pathophysiological relevance of protein dynamics in the regulation of GSEC function (Ch avez-Guti errez & Szaruga, 2020;Mehra & Kepp, 2021).…”
Section: Discussionsupporting
confidence: 77%